Making waves in the great ocean: A historical perspective on the emergence and evolution of wellbeing scholarship. Issue 2 (4th March 2022) - Lomas, Tim
ABSTRACT: The past 150 years have seen remarkable advances in the study of wellbeing. To appreciate the value and significance of these developments, this paper offers a historical perspective on their dynamics, arguing that we have seen four great waves of wellbeing scholarship in the modern West. I begin by exploring the wave metaphor itself, and then propose that these waves have been unfurling in a Western cultural 'ocean.' As such, I then explore key historical currents that have shaped this ocean, including Greek philosophy, Christianity, the Renaissance, and the Enlightenment. From there, the narrative considers the emergence of the first wave (psychiatry and psychotherapy), second wave (humanistic psychology), and third wave (positive psychology). The paper concludes by suggesting we are seeing an emerging fourth wave of 'global wellbeing scholarship, ' in which these Western waters are beginning to intermingle with other regional oceans (which have likewise progressed through their own developmental currents and waves), creating a more globally inclusive picture of wellbeing.